Formulation and release of alaptide from cellulose-based hydrogels - Sklenář, Zbyněk; Vitková, Zuzana; Herdová, Petra; Horáčková, Kateřina; Šimunková, Veronika (Acta veterinaria Brno, 2012)
The modern drug alaptide, synthetic dipeptide, shows regenerative effects and effects on the epitelisation process. A commercial product consisting of 1% alaptide hydrophilic cream is authorised for use in veterinary practice. This study focuses on the formulation of alaptide into semi-synthetic polymer-based hydrogels. The aim of the present study is to prepare hydrogels and to evaluate the liberation of alaptide from hydrogels. The hydrogels were prepared on the basis of three gel-producing substances: methylcellulose, hydroxyethylcellulose and hydroxypropylcellulose. To enhance the drug release from hydrogel humectants, glycerol, propylene glycol and ethanol in various concentrations were evaluated. The permeation of the alaptide from gels into the acceptor solution was evaluated with the use of the permeable membrane neprophane. The amount of drug released from prepared hydrogels was determined spectrophotometrically. Hydrogels with optimal alaptide liberation properties were subjected to the study of rheological properties in the next phase. The optimal composition of hydrogel as established in this study was 1% alaptide + 3% hydroxyethylcellulose with the addition of 10% glycerol as humectant. Due to the advantageous properties of hydrogels in wounds, alaptide could be incorporated into a hydrogel base for use in veterinary medicine.
Keywords: Animals; epitel; alaptid; Wound Healing; Hydrogels; Drug Liberation; Epithelium; dermatologické látky; celulosa; cyklické peptidy; Neuropeptides; hydrogely; hojení ran; farmaceutické pomocné látky; hormon inhibující uvolňování MSH; Peptides, Cyclic; neuropeptidy; MSH Release-Inhibiting Hormone; Pharmaceutic Aids; zvířata; uvolňování léčiv; zvlhčovadla; Cellulose; Dermatologic Agents